Spontaneous Resolution of Acute Rejection and Tolerance Induction With IL‐2 Fusion Protein in Vascularized Composite Allotransplantation. Issue 5 (12th February 2015) - Jindal, R.; Unadkat, J.; Zhang, W.; Zhang, D.; Ng, T. W.; Wang, Y.; Jiang, J.; Lakkis, F.; Rubin, P.; Lee, W. P. A.; Gorantla, V. S.; Zheng, X. X.
Abstract: Vascularized composite allotransplantation (VCA) has emerged as a treatment option for treating nonlife‐threatening conditions. Therefore, in order to make VCA a safe reconstruction option, there is a need to minimize immunosuppression, develop tolerance‐inducing strategies and elucidate the mechanisms of VCA rejection and tolerance. In this study we explored the effects of hIL‐2/Fc (a long‐lasting human IL‐2 fusion protein), in combination with antilymphocyte serum (ALS) and short‐term cyclosporine A (CsA), on graft survival, regulatory T cell (Treg) proliferation and tolerance induction in a rat hind‐limb transplant model. We demonstrate that hIL‐2/Fc therapy tips the immune balance, increasing Treg proliferation and suppressing effector T cells, and permits VCA tolerance as demonstrated by long‐term allograft survival and donor‐antigen acceptance. Moreover, we observe two distinct types of acute rejection (AR), progressive and reversible, within hIL‐2/Fc plus ALS and CsA treated recipients. Our study shows differential gene expression profiles of FoxP3 versus GzmB, Prf1 or interferon‐γ in these two types of AR, with reversible rejection demonstrating higher Treg to Teff gene expression. This correlation of gene expression profile at the first clinical sign of AR with VCA outcomes can provide the basis for further inquiry into the mechanistic aspects of VCA rejection and future drug targets. Abstract : The authors demonstrate that an IL‐2 fusion protein therapy promotes an increase in regulatory T cell proliferation and facilitates vascularized composite allograft tolerance.